Impact of post-thoracotomy analgesia with dexmedetomidine and morphine on immunocytes: a randomized clinical trial - Lei,Pengfei (2020)
Abstract Objective This study aimed to investigate the impact of post-thoracotomy analgesia with dexmedetomidine and morphine on immunocytes. Methods A total of 118 patients with post-thoracotomy Patient-Controlled Intravenous Analgesia (PCIA) in our hospital from March 2016 to July 2018 were randomly selected and divided into the Composite (COM) Group (57 patients administered with dexmedetomidine [1.0 µg.kg-1 body weight] and morphine [0.48 mg.kg-1 body weight]) and the Morphine (MOR) group (61 patients administered with morphine [0.48 mg.kg-1]). The values of lymphocyte subsets (CD3+, CD4+, and CD8+) and Natural Killer cells in the peripheral blood of these two groups were detected by FACSCalibur flow cytometry at different time points (before anesthesia induction [T0], immediately after tracheal extubation [T1], 12 hours after surgery [T2], 24 hours after surgery [T3], 48 hours after surgery [T4], 72 hours after surgery [T5], and 7 days after surgery [T6]). The doses of morphine at T3 to T5 and the adverse reactions between the two groups were also recorded and compared. Results The CD3+ level and the CD4+/CD8+ ratio at T2 to T5 and the CD4+ level and NK cells at T3 to T5 were significantly higher in the COM Group than in the MOR Group (p< 0.05). The postoperative morphine dose and the incidence of postoperative itching, nausea, and vomiting were significantly lower in the COM Group than in the MOR Group (p< 0.05). Conclusions Dexmedetomidine combined with morphine for post-thoracotomy PCIA can improve the function of immunocytes, reduce morphine consumption, and reduce the adverse reactions during analgesia induction.